2005
DOI: 10.1111/j.1365-2141.2005.05489.x
|View full text |Cite
|
Sign up to set email alerts
|

Chimaerism analyses and subsequent immunological intervention after stem cell transplantation in patients with juvenile myelomonocytic leukaemia

Abstract: Juvenile myelomonocytic leukaemia (JMML) is a clonal myeloproliferative disorder afflicting young children Hasle et al, 2003). Allogeneic haematopoietic stem cell transplantation (HSCT) is the only curative strategy and recent large studies indicate an event-free survival of approximately 50% following HSCT (Manabe et al, 2002;Locatelli et al, 2005). Despite the improvement in survival rate, relapse remains the most common cause of treatment failure, affecting one-third of patients (Manabe et al, 2002;Locatell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 32 publications
2
43
0
Order By: Relevance
“…First, our definition of increasing chimerism was based on the finding that a change between two longitudinal specimens that exceeded assay sensitivity, rather than the percentage increase in autologous signal, as published previously. [2][3][4][5][7][8][9] Second, the frequency of testing in our study was every 14 days in patients with MC, rather than weekly as in other reports. 2,7-9 Third, our samples might have contained a higher proportion of lymphocytes, as all of our patients received T-cell replete transplants, and 65% of our patients received peripheral blood stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, our definition of increasing chimerism was based on the finding that a change between two longitudinal specimens that exceeded assay sensitivity, rather than the percentage increase in autologous signal, as published previously. [2][3][4][5][7][8][9] Second, the frequency of testing in our study was every 14 days in patients with MC, rather than weekly as in other reports. 2,7-9 Third, our samples might have contained a higher proportion of lymphocytes, as all of our patients received T-cell replete transplants, and 65% of our patients received peripheral blood stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…2,[7][8][9] Use of DLI resulted in the long-term response in 5/20 children with ALL, 9/11 children with myelodysplastic syndrome, 1/6 children with juvenile myelomonocytic leukemia and 2/9 children with AML. 2,[8][9][10] Data in adults with AML showed that all 32 patients with increasing chimerism relapsed despite receiving immunomodulating therapy; 15 however, 4/8 patients with ALL who received DLI for MC showed long-term remission. 19 In 2000, Zetterquist et al 13 evaluated lineage-specific (CD19 þ ) chimerism in children with B-cell ALL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixed donor-chimerism after SCT in JMML has been shown to be an important predictor for relapse, therefore discontinuation of immunosuppressive therapy (IST) is the first step to prevent relapse if this occurs early after transplantation. 11 To avoid relapse, a second stem cell transplantation was considered, but the parents were very reluctant to proceed, because of the absence of any clinical signs of JMML and the excellent clinical condition of the child. Therefore, 6-mercaptopurine (6-MP) (average dose 40 mg/m 2 ) was started on day 145 after SCT.…”
Section: Hla-identical Umbilical Cord Blood Transplantation From a Simentioning
confidence: 99%